2021
DOI: 10.53730/ijhs.v5n3.2720
|View full text |Cite
|
Sign up to set email alerts
|

Public administration strategy of healthcare system for seniors

Abstract: The goal of the study is to restructure society’s attitude toward the needs of the elderly. The article addresses the methodology of state social policy and possible innovations in funding and economic methods for public administration in the healthcare system for seniors. The novelty of the work is ensured by the concept of managed older age and a start-up proposal to create the State Direct Investment Fund “Senior Generation” functioning as an entity responsible for the development of the organizational foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Studies have found that forests can reduce sadness; many studies have been carried out. Through walks in the forest, humans can get both physical and mental health, significantly reducing depression (Shamshurina et al, 2021). Strolling and exercising in the green and lush wilderness is ideal for managing medical conditions and reducing grief by taking walks with other people.…”
Section: Help Overweight and Back Shapementioning
confidence: 99%
“…Studies have found that forests can reduce sadness; many studies have been carried out. Through walks in the forest, humans can get both physical and mental health, significantly reducing depression (Shamshurina et al, 2021). Strolling and exercising in the green and lush wilderness is ideal for managing medical conditions and reducing grief by taking walks with other people.…”
Section: Help Overweight and Back Shapementioning
confidence: 99%
“…The rapid pace of technology implementation during the pandemic has also caused many problems related to medical personnel's training, changes in communication with patients, document management, financing. Due to the lack of funding for health institutions in countries (Joint decoration of the European Commission and who/Europe (who/Europe) "Partnerships for health in the who European Region" (2010), the implementation of technologies became a challenge that has largely declined during the crisis (Shamshurina et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For nurses, of course, extra patience is needed to be able to provide the best nursing services for the elderly (Kloppers et al, 2015). In order to be able to carry out the best nursing care for the elderly with all the existing obstacles, of course it takes the support of a positive attitude from the nurses [Shamshurina et al, 2021]. This is not easy, because attitudes cannot be built instantly in a short time.…”
Section: Discussionmentioning
confidence: 99%